The Difference of Zinc And Matrix Levels of Metalloproteinase-9 Serum Between Premature Rupture Of Membrane Aterm And Normal Pregnancy - Lisa Ernita; Ellyza Nasrul; Andi Friadi (Universitas Andalas, 2019)
Premature rupture of membranes (PROM) is one of the common problems in the obstetric field, ranging from 8-10% of term pregnancies will experience PROM. The increase in MMP-9 also has an impact on the degradation of the extracellular matrix and the apoptotic process of amniotic epithelial cells which ultimately leads to membrane rupture. The purpose of this study was to determine the differences in serum zinc and MMP-9 levels between premature rupture of membranes and normal pregnancies.This research is quantitative observational with the cross-sectional design carried out in Independent Practice Midwives for research samples of term premature rupture of normal and amniotic pregnancies, and Biomedical Laboratory of the Medical Faculty of Andalas University in March 2018 to March 2019. The research sample amounted to 35 respondents using consecutive sampling. Zinc and MMP-9 levels were examined by the Human ELISA Kit. Data analysis using the unpaired t-test.The results showed a mean serum zinc level of 13608 ± 1128.976µg / ml in Aterm KPD and 13799,111 ± 1254,335 µg / ml in normal pregnancies with p> 0.05. The mean serum MMP-9 levels were 1682.412 ± 320,398 ng / ml in Aterm PROM and 1807,667 ± 484,735 ng / ml in normal pregnancies with p <0.05.This study concludes that there is no difference in serum zinc levels in premature rupture of membranes and normal pregnancies; there is a difference in MMP-9 levels in premature rupture of membranes and normal pregnancy.